Ambulatory (24 h) blood pressure and arterial stiffness measurement in Marfan syndrome patients: a case control feasibility and pilot study. Issue 1 (December 2016) - Hillebrand, Matthias; Nouri, Ghazaleh; Hametner, Bernhard; Parragh, Stephanie; Köster, Jelena; Mortensen, Kai; Schwarz, Achim; von Kodolitsch, Yskert; Wassertheurer, Siegfried
Abstract Background The aim of this work is the investigation of measures of ambulatory brachial and aortic blood pressure and indices of arterial stiffness and aortic wave reflection in Marfan patients. Methods A case-control study was conducted including patients with diagnosed Marfan syndrome following Ghent2 nosology and healthy controls matched for sex, age and daytime brachial systolic blood pressure. For each subject a 24 h ambulatory blood pressure and 24 h pulse wave analysis measurement was performed. Results All parameters showed a circadian pattern whereby pressure dipping was more pronounced in Marfan patients. During daytime only Marfan patients with aortic root surgery showed increased pulse wave velocity. In contrast, various nighttime measurements, wave reflection determinants and circadian patterns showed a significant difference. Conclusions The findings of our study provide evidence that ambulatory measurement of arterial stiffness parameters is feasible and that these determinants are significantly different in Marfan syndrome patients compared to controls in particular at nighttime. Further investigation is therefore indicated.